Photodynamic therapy for recurrent basal cell skin carcinoma of the parietal region after radiotherapy - O. V. Matveeva (Biomedical Photonics)
The results of the clinical observation of patient with recurrent basal cell skin carcinoma of the parietal region occurred in 4 years after radiation therapy are represented. The patient underwent photodynamic therapy (PDT) using photosensitizer fotoditazin at a dose of 1.0 mg/kg; the laser power density was 0.45 W/cm2 , the laser energy density – 300 J/cm2 . Tolerability of the treatment was satisfactory. One year after treatment there was a cosmetically satisfying soft normotrophic scar with no attachment to underlying tissues in the site of the treatment of basal cell carcinoma. According to cytological study tumor cells were not detected. For five-year follow-up there was no recurrence.